2016
DOI: 10.1111/jace.14118
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transitions Induced by Ion Irradiation in V2AlC and Cr2AlC

Abstract: Nanolayered structural metallic ceramics, MAX phases, possess unique and highly attractive properties, including excellent radiation tolerance for some of them, whereas little is known about the detailed process of irradiation-induced structural transitions. In this study, the microstructural transformations and the stabilities of V 2 AlC and Cr 2 AlC induced by 1 MeV Au + ions irradiation over a wide range of fluences were investigated by grazing incidence X-ray diffraction (GIXRD) and transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 41 publications
(52 reference statements)
2
21
0
Order By: Relevance
“…Point defect calculations have only been performed on Cr 2 AlC where it is found that the Cr-Al antisite pair has the lowest formation energy of all possible point defect combinations thus providing a defect mechanism for recovery during irradiation 19 . This result, as well as the finding that the C Frenkel pair also has relatively low formation energy, is consistent with the recent observations on ion irradiated Cr 2 AlC 15, 16 . Although the calculations were based on summing the energies of the individual defects they showed that despite the low magnetic moment of Cr, a non-magnetic treatment of Cr 2 AlC is sufficient if only trends in defect formation behavior are required.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Point defect calculations have only been performed on Cr 2 AlC where it is found that the Cr-Al antisite pair has the lowest formation energy of all possible point defect combinations thus providing a defect mechanism for recovery during irradiation 19 . This result, as well as the finding that the C Frenkel pair also has relatively low formation energy, is consistent with the recent observations on ion irradiated Cr 2 AlC 15, 16 . Although the calculations were based on summing the energies of the individual defects they showed that despite the low magnetic moment of Cr, a non-magnetic treatment of Cr 2 AlC is sufficient if only trends in defect formation behavior are required.…”
Section: Introductionsupporting
confidence: 93%
“…Chromium is chosen as an alternative M element since it should enhance the high temperature oxidation resistance of the material 14 and has a lower neutron cross-section (3.1barn) than Ti. In addition Cr 2 AlC has been successfully synthesized and the main radiation induced defects have been determined 15, 16 . Depending on the processing conditions, small amounts of Cr 3 C 2 , Cr 7 C 3 and Cr 5 Al 8 can be present in the material 17 although generally speaking Cr 2 AlC has been synthesized (at the moment) with higher purity than Zr 2 AlC.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure of Cr–C–Cr still remains. Therefore, the decomposition products of Cr 2 AlC mainly consist of CrC x , and the results are supported by experiments …”
Section: Calculation Results and Discussionsupporting
confidence: 57%
“…Most of the recent investigations about Cr 2 AlC primarily focus on its synthesis and intrinsic properties . Some of the studies about irradiation resistance of Cr 2 AlC show that structural transition occurred and saturation of ion irradiation effects existed in Cr 2 AlC induced by irradiation using Xe, Au, and He ions . Theoretical calculations show that the unique properties of Cr 2 AlC are contributed to nanolaminated structure and the chemical bonding characters consisting of covalent, ionic and metallic .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation